A Broken Connection: A Screenplay about Psychosocial Problem Effects on People Living with HIV/AIDS - Charlie Gunawan; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2024)
This paper examines the impact of environmental behavior on individuals living with HIV/AIDS and its association with Psychosocial Problems. It focuses on the negative behavior which is exhibited by the environment towards individuals with HIV/AIDS, which can lead to adverse psychosocial outcomes. Psychosocial problems encompass the interaction between an individual's psychological well-being, social environment, and daily functioning, influenced by their environment and life events. The study acknowledges that external behavior plays a significant role in shaping internal behavior, and stressful events arising from negative external behavior can affect a person's internal well-being. The research centers on people who experience Psychosocial Problems as a result of rejection from family, friends, and society due to their HIV status. This work uses Social Cognitive theory to analyze the link of the effect of Psychosocial Problems with People Living with HIV/AIDS. As a result, this work highlights the profound impact of negative environmental behavior on individuals living with HIV/AIDS. Also, emphasize the need for supportive and accepting environments to mitigate psychosocial challenges in both psychological states in PLHIV.